PENGARUH KEAKTIFAN SISWA PADA PROGRAM TAHSIN TERHADAP KEMAMPUAN MEMBACA AL-QUR’AN - Al Farizi Al Farizi; Alimron Alimron; Dodi Irawan; Achmad Fadil (PAI RAFAH, 2022)
The activity of students in Al-Qur'an Tahsin program is the whole physical and non-physical learning process, such as listening to the Ustadz explaining the laws of recitation, and so on. This study aims to determine how active students are in Al-Qur'an Tahsin program at SMP Muhammadiyah 5 Palembang, how is the ability to read Al-Qur'an at SMP Muhammdiyah 5 Palembang, is there an effect of student activity in Al-Qur'an Tahsin program on the ability to read Al-Qur'an at SMP Muhammadiyah 5 Palembang.This study belongs to quantitative research which is regressive and uses simple statistical analysis techniques using percentage formula and product moment analysis techniques. The sample in this study was class VIII with a total of 99 students, 35% of which were randomly selected, so the sample was 35 students. In collecting data in this study using questionnaires and documentation.The results of this study can be seen from the data analysis, namely the correlation value of rxy calculation is 0.78, the correlation index number obtained is not negative, it can be said that there is a significant effect between variable x and variable y, then the rxy obtained is 0.78, which ranges between 0.70-0.90. Based on the above calculations, α = 0.05 and n = 35, one-sided test: Dk = n-2 = 35 - 2 = 33, resulting in t table = 1.692. It turns out that tcount> ttabe is 5.72> 1.692, then H0 is rejected, which means that there is a significant influence between students' activity in Al-Qur'an tahsin program on the ability to read Al-Qur'an at SMP Muhammadiyah 5 Palembang.